Paradigmatic Transformations in the Views of Jan Władysław Dawid: From Positivism to Mysticism - Ciechowska, Magdalena (Paedagogia Christiana, 2025)
Positivism and a strict approach to method – always and everywhere – or love of human souls? He was a collaborator with leading figures in experimental psychology, confessed a desire for a religious experience of the afterlife, and was a participant in spiritualist séances and an avid anti-cleric. Who was Jan Władysław Dawid, whose achievements contemporary educators still draw from? The biographies of few masters reflect such distant paradigms that are reflected in scientific work. Described as a scholar without a chair, he left behind several hundred publications that educators still use today. His early views in the spirit of positivism, at the end of his life, due to the tragic death of his wife, turn into mystical experiences. Researchers of his biography and achievements argue whether the path of these paradigmatic changes was continuous or whether there was a sudden change. The article presents this path, which is not shown in the course of students’ education. Meanwhile, in order to properly understand the literature being studied, it is necessary to know its creator.